2013
DOI: 10.1371/journal.pone.0058165
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Behavioral Changes in Honey Bees (Apis mellifera) Induced by Nosema ceranae Infection

Abstract: Persistent exposure to mite pests, poor nutrition, pesticides, and pathogens threaten honey bee survival. In healthy colonies, the interaction of the yolk precursor protein, vitellogenin (Vg), and endocrine factor, juvenile hormone (JH), functions as a pacemaker driving the sequence of behaviors that workers perform throughout their lives. Young bees perform nursing duties within the hive and have high Vg and low JH; as older bees transition to foraging, this trend reverses. Pathogens and parasites can alter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
202
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(220 citation statements)
references
References 53 publications
13
202
1
4
Order By: Relevance
“…There is evidence that precocious foragers are indeed heavier and less efficient flyers than older foragers [43]. This precocious foraging due to parasite infestation was previously observed in bees exposed to Nosema ceranae infestation [44].…”
Section: Discussionsupporting
confidence: 58%
“…There is evidence that precocious foragers are indeed heavier and less efficient flyers than older foragers [43]. This precocious foraging due to parasite infestation was previously observed in bees exposed to Nosema ceranae infestation [44].…”
Section: Discussionsupporting
confidence: 58%
“…It is known that N. apis affects the epithelial cells lining the midgut of the adult bees (Bailey, 1955) and shortens the life span of both queens and adult bees (Wang & Moeller, 1970;Webster, 1994). Recent studies (Huang, Solter, Aronstein, & Huang, 2015;Natsopoulou, Doublet, & Paxton, 2015) suggest that N. ceranae is not more virulent than N. apis, in disagreement with older studies which suggested that it was associating it with colony depopulation and collapse (Hatjina et al, 2010;Higes et al, 2008;Paxton, 2010;Paxton et al, 2007) as well as colony losses in general, in particular in southern European countries (Botías, Martín-Hernández, Barrios, Meana, & Higes, 2013;Dussaubat et al, 2013;Globlirsch, Huang, & Spivak, 2013;Hatjina et al, 2011;Higes, Martín-Hernandez, & Meana, 2010, 2006Higes et al, 2005Higes et al, , 2008Soroker et al, 2011;Villa, Bourgeois, & Danka, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both neonicotinoid insecticides and parasites alter associative learning and cognitive functions of bees [5][6][7][8][9]. Acting as nicotinic acetylcholine receptor (nAChR) agonists [10], exposure to very low levels of neonicotinoids can disrupt normal function of neurons in the bee brain [11,12] and lead to disruptions in learning and memory [8,13].…”
Section: Introductionmentioning
confidence: 99%